Effect of Fe doping and magnetic field on martensitic transformation of Mn-Ni(Fe)-Sn metamagnetic shape memory alloys. (15th August 2018) - Lázpita, P.; Sasmaz, M.; Barandiarán, J.M.; Chernenko, V.A.
Abstract: In this work we report the elaboration of a family of metamagnetic shape memory alloys with composition Mn49 Ni42-x Fex Sn9 (x = 0, 2, 3, 4, 5 and 6 at.%) and the systematic study of their structure, martensitic transformation (MT) behavior and functional characteristics as a function of the Fe doping and magnetic field, up to 12 T. Regarding the influence of the magnetic field, we have tentatively divided the alloys into two groups: group I, alloys with x = 0, 2, 3 and 4 and group II, alloys with x = 5 and 6. Group II alloys exhibit an appreciable amount of dispersed γ-phase and a field-induced arrest of MT. The alloys from group I show a large magnetization drop at MT that proceeds steeply. This group also displays a monotonous evolution of all studied properties with pronounced metamagnetic effect and large magnetostrain effect, reaching 0.3%, in the alloy with x = 4. Graphical abstract: Image 1